An illustrated textbook Ear, Nose and Throat Head and Neck Surgery - Guragain, R (Nepalese Journal of ENT Head and Neck Surgery, 2011)
DOI: 10.3126/njenthns.v1i1.4739 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.36